Bibliometric investigation of the integration of animal personality in conservation contexts - Sydney M. Collins; Jack G. Hendrix; Quinn M. R. Webber; Sean P. Boyle; Katrien A. Kingdon; Robert J. Blackmore; Kyle J. N. d'Entremont; Jennifer Hogg; Juan P. Ibáñez; Joanie L. Kennah; Jessika Lamarre; Miguel Mejías; et al. (Conservation Biology, 2023)
Consistent individual differences in behavior, commonly termed animal personality , are a widespread phenomenon across taxa that have important consequences for fitness, natural selection, and trophic interactions. Animal personality research may prove useful in several conservation contexts, but which contexts remains to be determined. We conducted a structured literature review of 654 studies identified by combining search terms for animal personality and various conservation subfields. We scored the relevance of personality and conservation issues for each study to identify which studies meaningfully integrated the 2 fields as opposed to surface‐level connections or vague allusions. We found a taxonomic bias toward mammals (29% of all studies). Very few amphibian or reptile studies applied personality research to conservation issues (6% each). Climate change (21%), invasive species (15%), and captive breeding and reintroduction (13%) were the most abundant conservation subfields that occurred in our search, though a substantial proportion of these papers weakly integrated conservation and animal personality (climate change 54%, invasive species 51%, captive breeding and reintroduction 40%). Based on our results, we recommend that researchers strive for consistent and broadly applicable terminology when describing consistent behavioral differences to minimize confusion and improve the searchability of research. We identify several gaps in the literature that appear to be promising and fruitful avenues for future research, such as disease transmission as a function of sociability or exploration as a driver of space use in protected areas. Practitioners can begin informing future conservation efforts with knowledge gained from animal personality research.